Covid-19 and Technology: Higher Education’s Responses to Inclusive Practices for Pre-Service Teachers with Disabilities - Edwin Darrell De Klerk; June Monica Palmer; Greg Alexander (Research in Social Sciences and Technology- OpenED Network, 2021)
Transforming the learning experiences of pre-service teachers with disabilities from stigma and social exclusion to experiencing a sense of belonging, is a desirable imperative for learning mediators in the South African Higher Education (SAHE) context. This paper presents a relational content analysis of the concepts, theories and policies, related to effecting transformation in the meaning schemes of pre-service teachers with disabilities and to provide HEIs with inclusive responses to addressing their learning support needs. The theory of perspective transformation, which highlights the process of effecting change in a frame of reference, is applied. The theory expands on three dimensions, including psychological (changes in understanding of the self), convictional (revision of belief systems) and behavioural (changes in lifestyle) with a sound foundation of inclusion aimed at drawing on practices for the prevention of exclusion of the pre-service teacher with disabilities in SAHE spaces. The paper further analyses discourses extracted from Section 47 of the Salamanca Statement, (1994) that build on inclusion artefacts in addressing perspective transformation. The findings in terms of belonging show that affirmations of the discourses, related to an interpersonal connection with others, have the scope to affect pre-service teachers with disabilities’ need for a positive regard as a prerequisite to foster the inclusion of individuals within any given relationship. This paper recommends that SAHE institutions embrace an ethos of inclusivity to achieve transformative equity for pre-service teachers with disabilities and offers an inclusive response framework to ensure that they are able to participate, learn and be welcomed as appreciated associates of HEIs.